Data Mining: Knowledge Discovery in Databases - Pandya, Dr. Maulik N.; Patel, Mr. Bhavin B. (IJRDO -Journal of Computer Science Engineering, 2016)
Database is a technology for data loading, storing, manipulating, querying, sharing and controlling.Leading-edge technology areas, such as data warehousing, web-based applications, object oriented databases,distributed databases, and front end tools are being increasingly utilized by organizations to manage large volumeof generated data and information like a Data Mining. This paper explores various statistics methods related withdata exploration. Data Exploration is mainly dependent upon the factors like (A) Summary statistics (B)Visualization (C) Online Analytical Processing (OLAP). Thus Data exploration is quite useful to understand thetrend, behavior of data and information provided by data mining techniques.